Pengaruh Beban Kerja, Kompensasi Langsung, dan Kompensasi Tidak Langsung terhadap Kepuasan Kerja pada PT. Bintang Baru Sentosa - Hardiansyah, Ahmad; Kusuma, Siska Fajar (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this research is to ascertain the impact of workload, direct compensation, and indirect compensation on employee job satisfaction at PT Bintang Baru Sentosa. The study employed a survey research method, collecting data through direct observation and the distribution of questionnaires in the research object's field. The participants in this research were PT Bintang Baru Sentosa employees, of which 50 employees made up the sample. This sampling used the saturated sampling method.The results of research using multiple linear regression analysis showed that partial workload, direct compensation and partial indirect compensation had a significant positive effect on job satisfaction for PT Bintang Baru Sentosa employees. Apart from that, simultaneously workload, direct compensation and indirect compensation have a significant positive effect on job satisfaction of employees at PT Bintang Baru Sentosa.